Decree No. 287 of the year 2015 on Imposing Final Precautionary measures On Imports of Reinforcing Steel for Building Purposes item ; Decree No. 288 of the year 2015 On Imposing Temporary Precautionary Measures On white Sugar Imports ; Decree No. 506 for the year 2015 Suspending Import of Scrap metal, Metal Junk, Iron slag and scum from Japan ; Decree No. 792 for the Year 2015 Determining Certain Customs Tax Exemption - Egypt (2025)
The Ministry of Industry, Trade and Small & Medium Projects Decree No. 287 of the year 2015 on imposing final precautionary Measures on imports of reinforcing steel for building purposes item – The Ministry of Industry, Trade and Small & Medium Projects Decree No. 288 of the year 2015 on imposing temporary precautionary Measures on white sugar imports – prime Minister’s decree no. 506 for the year 2015 amended by the rectification published in the official journal, issue no. 13, Dated 26/3/2015 – prime Minister’s decree no. 506 for the year 2015 determining certain customs tax exemptions وزارة الصناعة والتجارة والمشروعات الصغيرة والمتوسطة قرار رقم 287 لسنة 2015 بفرض تدابير وقائية نهائية على الواردات من صنف حديد التسليح لأغراض البناء – وزارة الصناعة والتجارة والمشروعات الصغيرة والمتوسطة قرار رقم 288 لسنة 2015 بفرض تدابير وقائية مؤقتة على الواردات من صنف السكر الأبيض – قرار رئيس مجلس الوزراء رقم 506 لسنة 2015 معدل بالاستدراك المنشور بالجريدة الرسمية العدد 13 فى 26/3/2015 – قرار رئيس مجلس الوزراء رقم 792 لسنة 2015 بتقرير بعض الإعفاءات من الضرائب الجمركية